Pelatihan Pengembangan Kreasi Dalam Hal Packaging Produk Sebagai Strategi Marketing Pada Usaha Kecil dan Menengah di Kelurahan Kembangan Selatan - Angela Dirman; Putri Dwi Wahyuni (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2020)
One strategy to increase consumer purchase interest is packaging design. The packaging is a "trigger" because its function is directly dealing with consumers. Therefore, packaging must be able to influence consumers to give a positive response, in this case buying a product; because the ultimate goal of packaging is to create sales. Paying attention to the surrounding area where it turns out that there are so many people who have a home-based business, we are motivated to provide training on creative development in product packaging as a marketing strategy. The implementation of this Community Service activity is carried out using the lecture, tutorial, and discussion methods. This activity was carried out in January 2020 at RPTRA Kembangan Selatan with a total of 34 peseta people. This service activity received a positive response from the participants, namely SME entrepreneurs and those who are new to working in UKM in the South Kembangan Region and the level of knowledge of the participants increased from before and after the training. Based on the results of the questionnaire given to the participants, it shows the level of satisfaction and response to the implementation of the high category activities. The participants hope that the same activities will be held regularly because they provide many benefits. Keywords: Packaging, Marketing strategy